CAN STILL IMAGES TELL STORIES? Symptom and temporality in photojournalism narrative theory - Casadei, Eliza Bachega [UNESP] (Sbpjor, 2015)
Temporality is one of the central concepts in defining narrative. In this sense, photojournalism has always been a problem for narratological studies, since traditional image theories understand photography as a figure that immobilizes time. The aim of this paper is to discuss if photojournalistic practice is able to engender narratives or whether it is merely linked to description. Since traditional theories, linked to the realm of visible, expel temporality of photojournalistic narratives, we must give it back time to the image from another record: the visual. Our argument is that it is in the interchange of visible with the visual that narrative and temporality is given in photojournalism, in an image conception that does not take into account only the semiotic elements of photojournalism, but also its symptomatic aspects.
Keywords: Narrative; Temporality; Symptom; Visible Visual